2022
DOI: 10.1093/ajcn/nqac283
|View full text |Cite
|
Sign up to set email alerts
|

Periconceptional folate intake influences DNA methylation at birth based on dietary source in an analysis of pediatric acute lymphoblastic leukemia cases and controls

Abstract: Background Periconceptional folate intake is associated with the establishment of DNA methylation in offspring; however, variations in this relationship by food sources versus folic acid supplements are not described. Also, maternal folate intake is associated with decreased risk of pediatric acute lymphoblastic leukemia (ALL), but the mechanism is not known. Objectives We evaluated the relationship between periconceptional f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Alternatively, the timing of a potential impact of folate-related nutrients on blood cell development and epigenome at large in the fetus may occur in early pregnancy, as shown in studies of nutritionally deprived women during early pregnancy [42,43], although no studies to date have directly tested this yet for childhood leukemia. Our group has recently published results on the relationship of DNA methylation patterns associated with periconception folate intake in children with ALL vs. healthy controls [10]. This epigenome-wide association analysis revealed a differentially methylated region (DMR) in the promoter region of DUSP22, a protein phosphatase and known tumor suppressor, in response to total and food periconceptional folate intake.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, the timing of a potential impact of folate-related nutrients on blood cell development and epigenome at large in the fetus may occur in early pregnancy, as shown in studies of nutritionally deprived women during early pregnancy [42,43], although no studies to date have directly tested this yet for childhood leukemia. Our group has recently published results on the relationship of DNA methylation patterns associated with periconception folate intake in children with ALL vs. healthy controls [10]. This epigenome-wide association analysis revealed a differentially methylated region (DMR) in the promoter region of DUSP22, a protein phosphatase and known tumor suppressor, in response to total and food periconceptional folate intake.…”
Section: Discussionmentioning
confidence: 99%
“…Childhood ALL exhibits a peak in incidence at the age of 2-5 years, and several experiments have demonstrated that chromosomal abnormalities detected at diagnostic were also identified at birth (such as ETV6-RUNX1, RUNX1-RUNX1T1, and PML-RARA gene fusions, as well as high hyperdiploidy), providing strong support to the prenatal origin of many childhood leukemia subtypes [4][5][6][7][8]. In addition, a recent study on discordant twins for ALL supports a role for DNA methylation alterations in utero impacting leukemogenesis [9]; such DNA methylation patterns may be influenced by periconceptional nutrients including folate [10]. In epidemiologic studies using interview data, prenatal folic acid and vitamin intake from dietary sources and supplementation [11][12][13][14][15] has consistently emerged as a protective factor for childhood leukemia.…”
Section: Introductionmentioning
confidence: 87%
“…REEP3 (#609348 OMIM) encodes Receptor Accessory Protein 3 (REEP3), which belongs to the Receptor Expression Enhancing Proteins (REEP) family. A recent study showed an association between the DNAm of REEP3 at birth and periconceptional folate intake [ 12 ]. A DMR located in an intergenic region, downstream of REEP3 (chr10:65733092-65733575), was shown to be one of the ten most responsive DMRs to folate supplementation [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed an association between the DNAm of REEP3 at birth and periconceptional folate intake [ 12 ]. A DMR located in an intergenic region, downstream of REEP3 (chr10:65733092-65733575), was shown to be one of the ten most responsive DMRs to folate supplementation [ 12 ]. While the DMR of the currently detected eQTM does not overlap directly, we hypothesize it could be highly relevant for FASD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Esses resultados estão em consonância com estudo desenvolvido por Timms et al, (2019), no qual a suplementação de folato promoveu a hipometilação de uma variedade de loci gênicos, atuando como fator protetor. Nickels et al, (2022), encontrou resultados semelhantes indicando uma hipermetilação do DNA em casos de LLA em crianças de famílias de origem hispânica com renda e nível educacional mais baixos. Sugerindo que, uma menor ingestão de folato total e alimentar durante a gestação associa-se ao desenvolvimento de leucemia.…”
Section: Fundamentação Teóricaunclassified